Survey of Health Status of Saveh Bakeries During COVID-19 Pandemic in 2020 - Rayhaneh Shahmohammadi; Tayebeh Rasolevandi; Hossein Azarpira (Mashhad University of Medical Sciences, 2021)
Abstract Background and Aim: Healthy food and nutrition play a key role in overcoming COVID-19 and achieving sustainable development. In most low- and middle-income countries, small companies, especially traditional food suppliers, have a fundamental role in the food supply chain, resulting in food and nutrition security. Materials and Methods: A checklist with 113 questions was designed including 57 questions on the conditions of COVID-19 derived from the second step guideline of fighting COVID-19 and 56 questions derived from regulation 111/920318. The total number of bakeries was 158 and the answers to the questions were recorded and analyzed as yes, no and not applicable. Results: In this study, based on the results obtained from the analysis of checklists, compliance of health status of different types of bakeries with regulations 111/920318 in Sangak, Barbari, Taftoon, Lavash and Baget (Nan Fantezie)  bakeries, was 73%, 79%, 87%, 76%, and 81% respectively Also, the percentage of compliance to the second step of the fight against Covid 19, was 65%, 71%, 69%, 73%, and 84%, respectively, and the compliance of the health status with final checklist in these bakeries was 69%, 75%, 78%, 74.5%, and 82.5%, respectively.  Conclusion: Health education and equipment hygiene were the least desirable in Sangak bakeries, food hygiene and health education were the least desirable in Barbari bakeries, food hygiene and health education were the least desirable in Taftoon bakeries, and in Lavash bakeries personal hygiene, food hygiene, and health education were least desirable. In Baget (Nan Fantezie) bakeries, the health conditions were significantly better than in traditional bakeries. Keywords: COVID-19; Pandemic; Checklist; Bakery; Health